Data lives : how data are made and shape our world - Kitchin, Rob (Bristol : Bristol University Press, 2021)
Rob Kitchin explores how data-driven technologies have become essential to society, government and the economy. Blending scholarly analysis, biography and fiction, he demonstrates how data influence our daily lives.
13 The End of the Data Lifecycle -- Part III Living with Data -- 14 Traces and Shadows -- 15 Recommended Life -- 16 The Quantified Self -- 17 Fighting Fires -- 18 Management Through Metrics -- 19 Guinea Pigs -- 20 Big Brother is Watching and Controlling You -- 21 Security Theatre -- 22 When a Country Ignores Its Own Data -- 23 Data Theft -- 24 Data for the People, by the People -- 25 Black Data Matter -- PART IV Conclusion -- 26 A Matter of Life and Death -- 27 Data Futures -- Notes -- Index -- Back Cover
Electronic resource, viewed: February 15, 2021.
Includes bibliographical references and index.
JSTOR
Keywords: Electronic data processing -- Social aspects; Information technology -- Social aspects; Technologie de l'information -- Aspect social; SOCIAL SCIENCE / Media Studies; Electronic data processing -- Social aspects; Information technology -- Social aspects; Electronic books; Electronic books